Design of modified microwave power divider for radar electronic warfare transceiving system - Mat Din, Amir Rudin (2007)
Radar electronic warfare beam forming transceiving system requires robust components in order to fully utilize the radar functionality. One such essential component is the power divider and its complementary power combining circuitry. Conventional power divider operates at a fundamental frequency and odd harmonics. The thesis presents the design of a broadband modified 2-way microwave power divider with the capability of delivering an identical signal as the backup to a radar electronic warfare transceiving system. The chosen band of the radar system is from 0.7 GHz to 3 GHz. The design starts with the basic conventional 2-way Wilkinson power divider. Modifications were done in the form of having trisection transmission lines and integrate it with either single or combination of lumped element loads of resistor, capacitor and inductor. The component values were initially computed. Investigations on the configurations were performed using an electromagnetic simulation software. It can be concluded that an optimum broadband modified power divider has been successfully designed to operate between 0.7 GHz to 3 GHz with equal power division of -3 dB at each output port.